Avaliação de enfermagem ao recém-nascido em uso de ventilação mecânica: intervenção para o desmame e extubação precoce - Barreira, Mary Anne Arraes (2002)
Work of quantitative approach Descriptive, it had as an object to investigate the New born(NB) in use of ventilation support equipment and the nursing problems that are indicates a step to wean precocious extubation. The datas were obtained by observations as end of systematic evaluations in two different moments: The first moment in the admission of nursing of the New born in the unit of intensive therapy, when they were identified problems; the degree of dependence of the care and the nurse's impression on New born. And the second moment, for occasion of the evaluation of RN in use of support ventilatório: nursing interventions for it weans himt and precocious extubation, which is based in five items: Identification, motivates that it provided the intubation, data indicators for extubation, procedures received pré, trans and powders extubation, application of the protocol for it weans him/it. The collection felt in the period of October and November of 2001, tends the study been accomplished with 20 RN. The analysis of the data was proceeded to the light of the Horta:s theory of the basic human needs . The datas reveal that the time of permanence of 20 RN in the ventilation mechanics was 20% weaned with less than 24 hours, 20% < 48:00: 30% < 96:00, and that 30% continued intubados for more than >96 hours being evidenced to be important the nurse's intervention during the process of it weans and extubation. Because he was considered that it continues the time of permanence of NB loud in use of support oxigen for more than 96 hours arriving up to 15 days of intubation in 30% of studied RN. It was evidenced that, if it turns vital the nurse's intervention for it weans him and extubation, when NB attends the vital oxigen. The study we seemed valid, in the sense of the concern for an evaluation method which should furn into a custom pratice in the units of intensive therapy for the NB, in special where the stady was realized.